A case report of perinatal arterial ischemic stroke: Silent cause behind neonatal seizures - Kumble, Ali; Phadke, Abhishek K; Varghese, Arun; Jacob, Manju (Indian Journal of Case Reports, 2025)
Perinatal arterial ischemic stroke (AIS) is a significant cause of neonatal seizures and long-term neurological morbidity, typically involving focal brain injury within an arterial territory. While most cases present in the neonatal period, some are diagnosed later as presumed perinatal AIS. We report a term male neonate, born via elective cesarean section to healthy, non-consanguineous parents with no identifiable risk factors. At 24 h of life, he developed right-sided focal seizures. Neurological and metabolic evaluations were unremarkable. Magnetic resonance imaging revealed an acute infarct in the left parietal lobe, insular cortex, and thalamus within the middle cerebral artery territory. Angiography was normal. Seizures were controlled with antiepileptics. This case highlights that perinatal AIS can occur even in low-risk neonates and may present solely as seizures. Timely neuroimaging and intervention are essential for accurate diagnosis and improved outcomes. A high index of suspicion is critical to minimizing long-term neurological sequelae.